The Role Of Risk Management Practices In The Success Of Software Outsourcing From The Perspective Of A Client Firm - Migeemanathan, James Sundararaj (2008)
The Information Technology (IT) outsourcing phenomenon had been maturing in recent years. Many organizations considered to outsource their IT functions such as software development activities to a third party vendor. However the success of such outsourcing decisions will not be guaranteed. It required some level of risk management practices to be in place to monitor and control the risk associated with outsourcing activities. This study was conducted to find out the role of risk management practices in ensuring the success of the outsourcing activities. Structured questionnaire was used in this study. It was distributed to 200 employees of the client firms. The data collected was statistically analyzed. The results showed that the relationship between nature of software outsourcing and the success of the software outsourcing project become stronger when the risk management practices is high.